Analysis of the Effect of Sharia Compliance and Islamic Corporate Governance on Fraud in Islamic Banks in Indonesia 2017-2019 - Hidayah Fazrin Milenia; Silvia Siska Pratiwi; Ade Wirman Syafei; Asri Noer Rahmi (Asia Pacific Fraud Journal, 2021)
This study aims to analyze the factors that influence the occurrence of fraud in Islamic banks in Indonesia. Measurement of fraud in Islamic banks is based on the number of internal frauds that occur in the financial year. The population in this study is Islamic banks in Indonesia for the period 2017-2019. The sample is selected using purposive sampling method and the number of samples obtained is 24 samples. The data used in this study are secondary data in the form of financial reports and corporate governance reports. Data analysis is performed using classical assumption tests and regression analysis. The results of this study indicate that Islamic corporate governance has a significant effect on internal fraud in Islamic banks in Indonesia. Meanwhile, partially the profit sharing ratio and Islamic investment ratio do not have a significant effect on internal fraud in Islamic banks in Indonesia. Islamic banking must comply with accounting standards and Auditing Organizations for Islamic Financial Institutions (AAOIFI) to minimize fraud in operations.